NOTE ON HYPEROSTOSIS IN THE PERCH POMADASYS HASTA (BLOCH) - Nammalwar, P (Indian Journal of Fisheries, 2011)
A case of hyperostosis in the skull bones of the perch, Pomadasys hasta, is reported. The oval-s.haped protuberance of frontal and supraoccipital bones of the skull and also a small depression between the eyes are very prominent. This gives to the skull a hump-like appearance